Cumulative domicide: The Sayisi Dene and destruction of home in mid-twentieth century Canada. (September 2020) - Basso, Andrew R; Ciaschi, Patrick; Akesson, Bree
This article introduces a new concept to help explain domicide perpetrated against one group of people over space and time: 'cumulative domicide'. The authors challenge the notion of domicide as an event and instead conceptualize the rights violation as a process. The cumulative domicide against the Sayisi Dene in Manitoba from the 1950s to the 1970s is a perfect illustration of the compounding, intergenerational effects that cumulative domicide can have upon a people when they are torn from their home and are not allowed to remake home elsewhere on their terms. In the case of the Sayisi Dene, the authors argue that processes of colonial expansion and hegemony are based on cumulative domicide and that this process occurs over variances in time and space.